The third rainbow girl [compact disc, unabridged] : the long life of a double murder in Appalachia - Eisenberg, Emma Copley (Hachette Book Group, 2020)
In the early evening of June 25, 1980 in Pocahontas County, West Virginia, two middle-class outsiders were hitchhiking to a festival known as the Rainbow Gathering, but never arrived. Using the past and the present, Eisenberg shows how this mysterious act of violence has loomed over all those affected for generations, shaping their fears, fates, and the stories they tell about themselves.